It's in the News: Developing a Real Time Index for Economic Uncertainty Based on Finnish News Titles - Aleksi Avela; Markku Lehmus (The Research Institute of the Finnish Economy (ETLA), 2020)
Uncertainty may affect economic behavior of individuals and firms in a wide variety of ways, with typically negative consequences for economic growth. It is due to this fact, combined with rising political uncertainty observed lately in many countries, that uncertainty has gained increasing attention in economic literature, too. In this paper, we construct a measure of economic uncertainty for Finland based on Finnish news titles, collected from the YLE's (the Finnish broadcasting company) website. To construct the index, we utilize machine learning and natural language processing (NLP) techniques, and in this paper, specifically, a transformed naive Bayes text classifier. On basis of the model evaluation, the constructed uncertainty index seems helpful in giving a timely assessment of the current state of the Finnish economy. We find a strong negative correlation between our index and the consumer confidence index by Statistics Finland, and most remarkably, our index seems to lead the consumer confidence index by one month.
Keywords: C45; C53; C61; E71; 330; Economic uncertainty; Nowcasting; Machine learning; Natural language processing; Naive Bayes